The Tetramethylpyrazine Derivative Statmp-151: A Novel Small Molecule Stat3 Inhibitor With Promising Activity Against Breast Cancer - Fan, Chen; Wang, Yijie; Huang, Hui; Li, Wenzhen; Ma, Jialin; Yao, Dongping; Tang, Zijun; Xue, Taixiong; Ha, Liyang; Ren, Yan; Zhang, Yiwen; Wang, Qin; et al. (Frontiers in Pharmacology, 2021)
Breast cancer is the most common malignancy in women and is a molecularly heterogeneous disease. Signal transducer and activator of transcription 3 (Stat3) is overexpressed and hyperactivated in a variety of human tumours, including breast cancer, thus representing a promising target for breast cancer treatment. In the present study, we evaluated the activities of a novel Stat3 inhibitor named Statmp-151 in the human breast cancer cell lines MCF-7 and MDA-MB-231 and the murine mammary carcinoma cell line 4T1. The in vitro results showed that Statmp-151 inhibited the proliferation of breast cancer cell lines in a dose- and time-dependent manner and suppressed the phosphorylation of Stat3 in a dose-dependent manner. Flow cytometry (FCM) assays revealed that Statmp-151 affected mitochondrial membrane potential and reactive oxygen species (ROS) production. Furthermore, Statmp-151 inhibited cell migration, as shown by analysis of the matrix metalloproteinases MMP2 and MMP9. Finally, in a 4T1 tumour-bearing mouse model, intraperitoneal injection of 30 mg/kg/day Statmp-151 significantly suppressed the growth of tumours without obvious toxicity. These results indicated that Statmp-151 might be a potential candidate for the treatment of breast cancer.